Phytochemical profiling and biological activities of Nigella sativa vinegar extract: an insight into hypoglycemic potential using in vivo and in silico studies - Akhtar, Muhammad Tahir; Qadir, Rahman; Altaf, Uzma; Almas, Tahira; Batool, Sajida; Ikram, Muhammad Salman; Meor Hussin, Anis Shobirin; Perveen, Kahkashan; Alshaikh, Najla A.; Saadia, Mubshara (John Wiley and Sons Inc, 2025)
The current study was conducted to characterize the vinegar extract of Nigella sativa and evaluate its biological activities using in vitro and in vivo studies. The N. sativa extract (NSE) was prepared by macerating seeds in a mixture of water and synthetic vinegar (1:10). The antioxidant potential of NSE was assessed, revealing high total phenolic contents (431.66 mg/100 g), total flavonoid contents (73.45 mg/100 g), total antioxidant capacity (118.55 mg/100 g), and strong radical scavenging potential (89.67%). The anticancer activity of NSE showed insignificant cytotoxic effects on HepG2 liver cell lines (96.61 ± 3.00). An in vivo animal trial was performed, and NSE significantly (p < 0.05) lowered the blood glucose (−47.71%), total cholesterol (−37.86%), total glycerides (39.42%), low-density lipoproteins (−29.36%), and very low-density lipoproteins (−30.60%), while increasing the high-density lipoproteins (26.92%) in alloxan-induced diabetic rats. GC–MS analysis of NSE revealed a diverse range of bioactive compounds, including alkaloids, phenolics, and flavonoids. In silico studies using molecular docking simulations showed that pyrrolo[1,2-a] pyrazine-1,4-dione, hexahydro-3-(2-methylpropyl) demonstrated a strong inhibitory action (6.6 kcal/mol) against alpha-amylase enzyme. These findings suggest that NSE is a promising natural remedy for managing diabetes and related metabolic disorders, and its potential as a nutraceutical ingredient in functional food applications is significant.